Case report for recurrent and new-onset SLE patients treated by high-dose glucocorticoid therapy: Characteristics of peripheral TCR beta chain CDR3 repertoires. Issue 49 (December 2017) - Yu, Jiang; Shi, Bin; Ma, Long; Liu, Chunmei; Sun, Suhong; Ma, Rui; Qiu, Yuehong; Yao, Xinsheng
Abstract: Rationale: High-dose glucocorticoid therapy has been widely applied in clinical practice in systemic lupus erythematosus (SLE)patients, but less is known about the changes of T cells, especially the T cell receptor (TCR) repertoires, during the treatment. The aim of this paper is to describe the changes of TCR that recurrent and new-onset SLE patients treated by high-dose glucocorticoid therapy. Patient concerns: Drugs of clinical treatment of SLE mainly include glucocorticoid, immunosuppressive agents, nonsteroidal anti-inflammatory drugs and B cell targeted drugs, etc, but the clinical symptoms were in remission and recurrent of onset patients with SLE. Diagnoses: Refer to the diagnostic criteria for SLE in 2011 by the American society of rheumatology. Interventions: All patients were treated with High-dose glucocorticoid therapy and surveyed the TCR repertoires at 3 monitoring moments (before treatment, one month after treatment, and 3 months after treatment) to analyze the relationship between the characteristics of TCR repertoire and the highdose glucocorticoid therapy. Outcomes: We found that high-dose glucocorticoid therapy resulted in clinical symptom remission, as well as change of diversity, highly expanded clones (HEC), usage of TCR beta chain variable gene (TRBV)/TCR beta chain joining gene (TRBJ), and overlapped sequences of TCR beta chain complementarity determining region 3 (CDR3) repertoires. This suggests that the effect of high-dose glucocorticoids on TCR repertoires is closely related to individual autoimmune T cells. Lessons: In this study, we have shown that we could evaluate the effect of therapy, the pathogenesis, and the prognosis for the patients with SLE by monitoring the TCR CDR3 repertoires. It could afford a new method to find the therapeutic target of SLE. Abstract : Supplemental Digital Content is available in the text